Method for doping titanium dioxide nanotube array - LIU GUOGUANG; LIU HAIJIN (2009)
The invention discloses a method for doping a titanium dioxide nanotube array and aims to provide a low-cost and high-doping-efficiency method for doping a titanium dioxide nanotube array. The method comprises the following steps: placing the titanium dioxide nanotube array to be doped and a platinum electrode in an electrolysis bath; and connecting the positive pole and the negative pole of a direct current power supply and the platinum electrode and the titanium dioxide nanotube array to be doped respectively, wherein the voltage of the direct current is no more than 10 V and the electrolyte is a salt solution containing NH4 or a mixed salt solution containing metal ions and NH4. Compared with the prior art, the method has the obvious advantages of low implement cost, convenient operation, high doping efficiency, and the like. The method is suitable for doping nanotubes.